Genomic and phenotypic characterization of two novel human-derived Limosilactobacillus reuteri strains with unique probiotic traits - Yang, Lijuan; Zhan, Hongyu; Wu, Xiaoyu; Wang, Aoqi; Zou, Yi; Li, Jinjin; Lu, Yongjun; Ge, Zhenhuang (Frontiers in Microbiology, 2025)
BackgroundLimosilactobacillus reuteri is recognized for its diverse host-beneficial functions, though these are highly strain-specific. This study aimed to genomically and functionally characterize two novel L. reuteri isolates to assess their potential for specific health-associated applications.MethodsWe isolated and genomically sequenced two novel L. reuteri strains, LLR2 and LLR3. Their functional potential was systematically evaluated through in vitro assays, including assessment of reuterin production, the ability to stimulate mucin production in co-culture with intestinal epithelial LS174T cells, and anti-inflammatory activity in a human brain microvascular endothelial cell (hCMEC/D3) model of LPS-induced inflammation.ResultsComparative genomic analysis revealed distinct genetic architectures between LLR2 and LLR3, reflecting divergent evolutionary trajectories. Functionally, pronounced strain-specific differences were observed: LLR3 produced the antimicrobial compound reuterin, while LLR2 did not. In co-culture with LS174T cells, both strains decrease the production of Mucin-2, a key component of the gut barrier, with LLR2 showing significantly greater efficacy. Conversely, in the hCMEC/D3 inflammation model, LLR3 demonstrated a significantly stronger anti-inflammatory effect, suppressing the LPS-induced expression of IL-6 and TNF-α.ConclusionThis study expands the genomic repository of L. reuteri and provides clear experimental evidence of strain-specific functional profiles. Our findings establish a foundation for the precision selection of L. reuteri strains such as LLR2 for gut barrier reinforcement and LLR3 for inflammation modulation in tailored applications for gut health and gut-brain axis research.